2020
DOI: 10.1101/2020.10.09.332619
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adeno-associated virus capsid assembly is divergent and stochastic

Abstract: Adeno-associated viruses (AAVs) are small, non-enveloped, and have a T=1 icosahedral capsid. They belong to the Parvoviridae, genus Dependoparvovirus. Interest in AAVs has grown over recent years as they have emerged as promising gene therapy vectors. The AAV capsid, encapsulating the transgene, consists, in total, of 60 subunits made up from three distinct viral proteins (VPs) originating from the same cap gene (VP1, VP2, and VP3), which vary only in their N-terminus. While all three VPs play a crucial and sp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…Development of HPLC assays for adeno-associated virus (AAV) must accommodate a more challenging reality. Individual AAV capsids comprise 60 capsid proteins of 3 types, ideally but often not in a ratio of 1:1:10; which may lack encapsidated DNA or contain DNA of varying lengths, with varying proportions of single-stranded and double-stranded sequences [ 1 , 2 , 3 ]. Post-translational modifications impose additional layers of heterogeneity [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of HPLC assays for adeno-associated virus (AAV) must accommodate a more challenging reality. Individual AAV capsids comprise 60 capsid proteins of 3 types, ideally but often not in a ratio of 1:1:10; which may lack encapsidated DNA or contain DNA of varying lengths, with varying proportions of single-stranded and double-stranded sequences [ 1 , 2 , 3 ]. Post-translational modifications impose additional layers of heterogeneity [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individual AAV capsids comprise 60 capsid proteins of 3 types, ideally but often not in a ratio of 1:1:10; which may lack encapsidated DNA or contain DNA of varying lengths, with varying proportions of single-stranded and double-stranded sequences [ 1 , 2 , 3 ]. Post-translational modifications impose additional layers of heterogeneity [ 3 , 4 , 5 ]. AAV cell harvests and lysates bear contaminant species and levels similar to those encountered with recombinant protein cell culture harvests but AAV levels are orders of magnitude lower, leaving AAV virtually a trace component in an overwhelming excess of contaminants [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that capsid f FIGURE 5 Centrifugram of the empty capsid peak from AEX after AEX of CEX-purified AAV. composition frequently varies from the ideal virus protein ratios of 1 VP1 to 1 VP2 to 10 VP3 [24], and that post-translational deamidation can substantially alter capsid surface charge [25]. The ramp region might contain such variants.…”
Section: Chromatograms From Initial Cex Purification Of Aav8 (A) and Subsequent Separation Of Empty And Full Capsids By Aex (B)mentioning
confidence: 99%
“…To date, a variety of methods have been used to quantify empty and full AAV capsids, which include UV/Vis spectroscopy and capsid (cp)-to-vector genome (vg) titer ratio, 8 transmission electron microscopy (TEM), 9 analytical ultracentrifugation (AUC), 10 size exclusion chromatography coupled to multiangle light scattering (SEC-MALS), 11 capillary electrophoresis, 12 mass photometry, 13 and mass spectrometry (MS). [14][15][16] Each method utilizes a unique approach toward addressing the quantification of the empty-to-full ratio of an AAV capsid. Each method, however, also has shortcomings.…”
Section: Introductionmentioning
confidence: 99%